1997
DOI: 10.1111/j.1432-1033.1997.0240a.x
|View full text |Cite
|
Sign up to set email alerts
|

The Phosphatidylinositol 3‐Kinase Inhibitors Wortmannin and LY294002 Inhibit Autophagy in Isolated Rat Hepatocytes

Abstract: The phosphatidylinositol 3-kinase inhibitors wortmannin and LY294002 inhibit autophagy in isolated rat hepatocytes Blommaart, E.F.C.; Krause, P.; Schellens, J.P.M.; Vreeling-Sindelárová, H.; Meijer, A.J. Published in:European Journal of Biochemistry DOI:10.1111/j. 1432-1033.1997.0240a.x Link to publication Citation for published version (APA): Blommaart, E. F. C., Krause, P., Schellens, J. P. M., Vreeling-Sindelárová, H., & Meijer, A. J. (1997). The phosphatidylinositol 3-kinase inhibitors wortmannin and LY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
596
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 783 publications
(630 citation statements)
references
References 42 publications
33
596
0
1
Order By: Relevance
“…8). This is in accordance with data previously reported for hepatocytes [20,42] and other cells [43,44]. This is conceivably because the IC 50 value (the concentration causing the half-maximal inhibition) is 10-fold smaller for cell-free preparations than for intact-cell preparations as a result of limited permeability of plasma membranes to the inhibitor [24].…”
Section: Involvement Of Specific Receptors In the Egf Actions Observesupporting
confidence: 92%
“…8). This is in accordance with data previously reported for hepatocytes [20,42] and other cells [43,44]. This is conceivably because the IC 50 value (the concentration causing the half-maximal inhibition) is 10-fold smaller for cell-free preparations than for intact-cell preparations as a result of limited permeability of plasma membranes to the inhibitor [24].…”
Section: Involvement Of Specific Receptors In the Egf Actions Observesupporting
confidence: 92%
“…It has long been known that 3-MA inhibits autophagy, 26 and it was recently found to be an inhibitor of PI3K. 27 PI3K is a conserved family of lipid kinases that catalyze the phosphorylation of the position 3 of the inositol ring of phosphoinositides. [28][29][30] They produce lipids that are involved in cell proliferation, differentiation, apoptosis, autophagy, cytoskeletal organization, and membrane trafficking.…”
Section: Discussionmentioning
confidence: 99%
“…13 Amino-acid stimulation of S6 phosphorylation was inhibited by the phosphatidylinositol 3-kinase (PI3K) inhibitors wortmannin or LY294002. 26 Unexpectedly, and in contrast to the effect of rapamycin, these two compounds inhibited autophagy in the absence of amino acids. 26 The explanation of this apparent anomaly was found by a study carried out with HT-29 cells, a human colon cancer cell line.…”
Section: Inhibition Of Autophagy By Amino Acidsmentioning
confidence: 94%
“…26 Unexpectedly, and in contrast to the effect of rapamycin, these two compounds inhibited autophagy in the absence of amino acids. 26 The explanation of this apparent anomaly was found by a study carried out with HT-29 cells, a human colon cancer cell line. These experiments have shown that the product of class-III PI3K, phosphatidylinositol 3-phosphate (PI(3)P), is required for autophagy, whereas the products of class-I PI3K, phosphatidylinositol 3,4, bisphosphate (PI(3,4)P 2 ), and phosphatidylinositol-3,4,5-trisphosphate (PI(3,4,5)P 3 ), have inhibitory effects.…”
Section: Inhibition Of Autophagy By Amino Acidsmentioning
confidence: 94%